2021
DOI: 10.3389/fpsyg.2021.652673
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Nigerian Dùndún Talking Drum Performances as Speech-Like vs. Music-Like: The Role of Familiarity and Acoustic Cues

Abstract: It seems trivial to identify sound sequences as music or speech, particularly when the sequences come from different sound sources, such as an orchestra and a human voice. Can we also easily distinguish these categories when the sequence comes from the same sound source? On the basis of which acoustic features? We investigated these questions by examining listeners’ classification of sound sequences performed by an instrument intertwining both speech and music: the dùndún talking drum. The dùndún is commonly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…To a large extent, a Yorùbá speaker is aware when a drummer a switches from purely musical rhythm to speech-like rhythm and vice versa. This is established in the perceptual experiment of Durojaye et al (2021a). The logical move for future reseaarch is to compare the rhythm of Yorùbá speech and song to the rhythm of the (un)interpreted portions of the videogame music (as in Patel and Daniele, 2003).…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…To a large extent, a Yorùbá speaker is aware when a drummer a switches from purely musical rhythm to speech-like rhythm and vice versa. This is established in the perceptual experiment of Durojaye et al (2021a). The logical move for future reseaarch is to compare the rhythm of Yorùbá speech and song to the rhythm of the (un)interpreted portions of the videogame music (as in Patel and Daniele, 2003).…”
Section: Discussion Summary and Conclusionmentioning
confidence: 99%
“…Previous studies suggests that consumers of speech surrogates rely on pitch contour and context in their interpretation of the messages encoded with speech surrogates (Villepastour, 2010;Sotunsa, 2021), but the possibility of simply interpreting speech-surrogate messages based on previous experience and associated meaning cannot be ruled out. For example, the findings of Durojaye et al (2021a) indicates that familiarity with speech surrogacy plays a role in distinguishing speech mode from song mode. Though Durojaye et al (2021a) is about the categorisation of Yorùbá drum stimuli as music-like or speech-like, their finding is relevant to the interpretation of speech-surrogate messages.…”
Section: Language Background: Yor ùBá and Its Talking Drummentioning
confidence: 99%
See 1 more Smart Citation
“…), it is challenging to analyze and compare key structural aspects such as pitch intervals, pitch contour shape, or note/syllable duration. While automatic segmentation can be effective for segmenting some musical instruments and animal songs (e.g., percussion instruments [Durojaye et al, 2021]; bird song notes separated by micro-breaths [Roeske et al 2020]), we found they did not provide satisfactory segmentation results compared to human manual annotation for the required task of segmenting continuous song/speech into discrete acoustic units such as notes or syllables (cf. Fig.…”
Section: Introductionmentioning
confidence: 90%
“…Although we can find studies showing higher brightness in singing performed by professional singers (Barnes et al, 2004;Merrill & Larrouy-Maestri, 2017;Sharma et al, 2021;Sundberg, 2001), our dataset does not necessarily consist of recordings by professional musicians and as in the case of Stone et al (1999) the prominent use of the high formant frequencies in singing may depend on musical style (but see Nikolsky et al, (2020) for the role of timbre played in personal music tradition). However, we would like to note that other aspects of timbre such as noisiness (spectral flatness) can potentially indicate the difference between song and speech (Durojaye et al, 2021).…”
Section: S12 Hypotheses For Speech-song Similaritiesmentioning
confidence: 99%